Аналіз ефективності амбулаторного спостереження хворих на цукровий діабет 2-го типу - Хуторська, Л. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
The paper presents the results of studying the actual management of patients with type 2 diabetes mellitus (DM) receiving oral glucose-reducing agents. The case reports of 290 patients with type 2 DM were analyzed. Poor adherence to the international and Ukrainian guidelines for the management of type 2 DM, unsatisfactory control of cardiovascular risk factors, and untimely correction of glucose-reducing therapy were revealed.